Effect of Plant Extracts and Essential Oil Blend as Alternatives to Antibiotic Growth Promoters on Growth Performance, Nutrient Utilization and Carcass Characteristics of Broiler Chicken - Devi, Pebam Chandrima; Samanta, A. K. (Indian Journal of Animal Nutrition, 2018)
A study was conducted to assess the effect of dietary supplementation of plant extracts and essential oils on performance of broiler birds, nutrient utilization and carcass traits of broiler birds. Â Two hundred one day old broiler chicks were randomly distributed into five treatment groups with five replicates containing eight birds in each replicates. Dietary groups consisted of : 1) basal diet Â as per BIS standard ,2007 without any supplementation (control); 2) basal diet with BMD (Bacitracin methylene disalicylate) @.5g/kg of feed (AB); 3) basal diet supplemented with methanolic extracts of Mikania micrantha and Garcinia lanceaefolia @ 2.79 g/kg and 1.39 g/kg of feed respectively. 4) basal diet supplemented with Essential oil (Cinnamon and ajawain @ 3 g/kg and 4 g/kg of feed respectively; and 5) basal diet with plant extracts and essential oil combination at same dose rate. Metabolic trial was conducted at the end of feeding trial . One chicken from each replicate was slaughtered for measurement of carcass traits. Broiler birds fed AB, PE, EO and PEO increased (P